Environmental fate of pesticides in open field and greenhouse tomato production regions from Colombia - Luis Alejandro Arias; Alejandra Garzón; Alejandra Ayarza; Sandra Aux; Carlos Ricardo Bojacá (Environmental Advances, 2021)
The environmental fate of pesticides has been widely studied in temperate regions but not in tropical regions. In Colombia, tomato is an important commodity characterized by the excessive use of pesticides; however, the environmental fate of pesticides has not yet been determined. Residues for 30 pesticides were analyzed in fruits, leaves, and soils samples, as well as residues for 490 pesticides in water and sediments, from two open field and greenhouse tomato production regions, by direct sampling in the field and subsequent laboratory analysis through liquid or gas chromatography coupled to mass spectrophotometry. A total of 22 pesticides were detected, being the highest concentrations for thiocyclam in fruits (0.79 mg kg−1), indoxacarb in leaves (24.81 mg kg−1) and dimethomorph in soils (44.45 mg kg−1), however no residues were detected in water or sediments. At least one pesticide was detected in 66.7% of the samples. Methomyl and dimethomorph were common in fruits, leaves and soils for both regions; in addition, seven pesticides exceeded the Maximum Residue Limits. The results showed a high presence and affinity of pesticides in the environmental compartments of high-Andean tomato production regions, mainly in soils and open field productive systems.